Modulation of vascular contraction via soluble guanylate cyclase signaling in a novel ex vivo method using rat precision‐cut liver slices. Issue 3 (20th May 2021) - Oldenburger, Anouk; Birk, Gerald; Schlepütz, Marco; Broermann, Andre; Stierstorfer, Birgit; Pullen, Steven S.; Rippmann, Jörg F.
Abstract: Fibrotic processes in the liver of non‐alcoholic steatohepatitis (NASH) patients cause microcirculatory dysfunction in the organ which increases blood vessel resistance and causes portal hypertension. Assessing blood vessel function in the liver is challenging, necessitating the development of novel methods in normal and fibrotic tissue that allow for drug screening and translation toward pre‐clinical settings. Cultures of precision cut liver slices (PCLS) from normal and fibrotic rat livers were used for blood vessel function analysis. Live recording of vessel diameter was used to assess the response to endothelin‐1, serotonin and soluble guanylate cyclase (sGC) activation. A cascade of contraction and relaxation events in response to serotonin, endothelin‐1, Ketanserin and sGC activity could be established using vessel diameter analysis of rat PCLS. Both the sGC activator BI 703704 and the sGC stimulator Riociguat prevented serotonin‐induced contraction in PCLS from naive rats. By contrast, PCLS cultures from the rat CCl4 NASH model were only responsive to the sGC activator, thus establishing that the sGC enzyme is rendered non‐responsive to nitric oxide under oxidative stress found in fibrotic livers. The role of the sGC pathway for vessel relaxation of fibrotic liver tissue was identified in our model. The obtained data shows that the inhibitory capacities on vessel contraction of sGC compounds can be translated to published preclinical data. Altogether, this novel ex vivo PCLS method allows for the differentiation of drug candidates and the translation of therapeutic approaches towards the clinical use. Abstract : Cultures of rat precision cut liver slices (PCLS) were used for ex vivo blood vessel function analysis via live recording. The sGC activator BI703704 differentiates from the sGC stimulator Riociguat in the prevention of serotonin induced blood vessel contraction of normal and fibrotic rat liver slices. ​